Analysis of Paylater Customer Intentions in E-Commerce with the Planned Behavior Method Theory Approach - Kamal, Al Haq; Cheumar, Mohammad Tahir; Hasanah, Hasanah; Sudibyo, Tyagita Dianingtyas (Al-Mashrof: Islamic Banking and Finance, 2023)
This study aims to examine the effect of attitudes on behavior, subjective norms, perceived behavioral control, behavioral intentions, and behavior in implementing the shopee paylater payment system (buy now pay later) in generation Z in Caturtunggal, Depok, Sleman, Yogyakarta. This research is descriptive quantitative. The population in this study is generation Z with criteria ranging from 18 years to 30 years who have or are currently buying products at e-commerce shopee using the paylater payment system. The sampling technique used purposive sampling with a total sample of 100 respondents. The type of data used is primary data obtained by distributing questionnaires through questionnaires. The data analysis technique used is the Partial Least Square (PLS) approach using Smartpls 4 software. The results of the research based on the analysis of the regression coefficients (t-statistics and p-value) show that the attitude variable has a negative and insignificant effect on the behavioral intention variable. subjective norm variable has a negative and insignificant effect on behavioral intention variable. the variable perceived behavioral control has a negative and insignificant effect on the behavioral intention variable. perceived behavioral control variables have a positive and significant effect on behavioral variables. Then the behavioral intention variable has a positive and significant effect on the behavior variable or generation Z behavior.